2002
DOI: 10.1073/pnas.102091699
|View full text |Cite
|
Sign up to set email alerts
|

From flies' eyes to our ears: Mutations in a human class III myosin cause progressive nonsyndromic hearing loss DFNB30

Abstract: Normal vision in Drosophila requires NINAC, a class III myosin. Class III myosins are hybrid motor-signaling molecules, with an Nterminal kinase domain, highly conserved head and neck domains, and a class III-specific tail domain. In Drosophila rhabdomeres, NINAC interacts with actin filaments and with a PDZ scaffolding protein to organize the phototransduction machinery into a signaling complex. Recessive null mutations in Drosophila NINAC delay termination of the photoreceptor response and lead to progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
194
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(200 citation statements)
references
References 19 publications
2
194
1
3
Order By: Relevance
“…Preparations enriched for photoreceptor inner/outer segments (shake-offs) were twofold enriched for Myo3A over retina, consistent with the immunohistochemical observation that retinal Myo3A is localized almost exclusively to photoreceptor inner segments. Myo3A was also detected in the bass sacculus on Western blots, confirming in situ hybridization results in fetal mouse cochlea (Walsh et al, 2002). We have also used RT-PCR to amplify MYO3A from a human fetal cochlear library (Dosé, A.C., unpublished results).…”
Section: Expression Patterns and Cellular Localizationmentioning
confidence: 57%
See 1 more Smart Citation
“…Preparations enriched for photoreceptor inner/outer segments (shake-offs) were twofold enriched for Myo3A over retina, consistent with the immunohistochemical observation that retinal Myo3A is localized almost exclusively to photoreceptor inner segments. Myo3A was also detected in the bass sacculus on Western blots, confirming in situ hybridization results in fetal mouse cochlea (Walsh et al, 2002). We have also used RT-PCR to amplify MYO3A from a human fetal cochlear library (Dosé, A.C., unpublished results).…”
Section: Expression Patterns and Cellular Localizationmentioning
confidence: 57%
“…We have reported the cloning of two human class III myosins: MYO3A, cloned from the human retina and retinal pigment epithelium (RPE) (Dosé and Burnside, 2000), and MYO3B, cloned from the human retina (Dosé and Burnside, 2000;Berg et al, 2001). It was recently shown that human MYO3A is a target for nonsyndromic progressive hearing loss (Walsh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…20 MYO15A mutations were discovered concomitantly in human DFNB3 families and in the shaker 2 mouse. 12,21 In the Middle Eastern Jewish and Arab populations, to date, eight mutations have been reported in myosins IIIA, 7 myosin VIIA 22 and myosin XVA. 3,22 The present study, using targeted capture and MPS, defines nine novel mutations in MYO6, MYO7A and MYO15A, doubling the number of myosin mutations present in the Middle East responsible for non-syndromic hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…In the cochlea, the protein is present along the stereocilia, close to the junction between hair cells and supporting cells and present in the synaptic region, Gene MYO7A, located in chromosome 11 (11q13.5), has 49 exons that codify non-conventional myosin protein VIIA (2215 amino acids). 6 Mutations in the gene cause structural defects of the protein and consequent affections in auditory function, 10 Mutations determine DFNB30, characterized by bilateral progressive hearing loss that affects primarily high frequencies, starting on the second decade, and at age 50 years, it reaches severe level in high and medium frequencies and moderate level in low frequencies. 10 2) Harmonin: gene site, if mutant, causes DFNB18, and was mapped at chromosome 11 (11p15.1), at the same gene location as USH1C (Usher Syndrome Type IC11p15.1).…”
Section: Molecular Genetics Of Non-syndromic Hearing Lossmentioning
confidence: 99%
“…6 Mutations in the gene cause structural defects of the protein and consequent affections in auditory function, 10 Mutations determine DFNB30, characterized by bilateral progressive hearing loss that affects primarily high frequencies, starting on the second decade, and at age 50 years, it reaches severe level in high and medium frequencies and moderate level in low frequencies. 10 2) Harmonin: gene site, if mutant, causes DFNB18, and was mapped at chromosome 11 (11p15.1), at the same gene location as USH1C (Usher Syndrome Type IC11p15.1). 7,11 Gene USH1C (28 exons) codifies a protein that contains domain PDZ, denominated harmonin.…”
Section: Molecular Genetics Of Non-syndromic Hearing Lossmentioning
confidence: 99%